Toxic response of three predatory fishes to four indigenous plant seed extracts - Nasiruddin, Munira; Azadi, Mohammad Ali; Rahman, Tania; Ashrafunnessa, Mst (Chittagong University Journal of Biological Sciences, 2013)
Toxicity of seed extracts of four indigenous plants, Luffa acutangula (Roxb.), Areca catechue (Linn.), Brassica nigra (Linn. Koch.) and Brassica hirta (Monech) was tested on three predatory fishes- Heteropneustes fossilis (Bloch), Anabas testudineus (Bloch) and Channa punctatus (Bloch) under normal laboratory conditions. Due to the toxic effect of different seed extracts and concentrations, mortality rate varied. It also varied from species to species. On the basis of LC50 values of absolute ethyl alcohol extracts, L. acutangula seed extracts were more toxic for H. fossilis and A. testudineus. A. catechue seed extracts were of medium toxicity for all the experimental fishes. B. nigra seed extracts were less toxic whereas B. hirta seed extracts showed differential toxicity being more toxic for C. punctatus, medium for A. testudineus and less toxic for H. fossilis. The susceptibility pattern also varied in the three fish species. In case of L. acutangula, A. catechue and B. nigra seed extracts, the susceptibility was in the same order: H. fossilis > A. testudineus > C. punctatus but the effect of B. hirta seed extracts was reverse. To determine the ichthyotoxicity of the four seed extracts on the three predatory fishes, the present study was undertaken. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17079 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):27-39, 2011